E-WOM, SERVICE FEATURES, DAN FREE DELIVERY: SEBERAPA KUATKAH DALAM MEMPENGARUHI BUYING DECISION - Nurchasanah, Devi; Lukitaningsih, Ambar; Cahyani, Putri Dwi (Jurnal Manajemen Terapan dan Keuangan, 2024)
The study assessed the impact of electronic word-of-mouth (E-WOM), service characteristics, and free delivery on consumer purchasing decisions. The focus group consisted of Shopee users living in Yogyakarta Special District, with a total of 112 people selected through intentional sampling. The data was collected using a digital survey completed by participants through Google Forms and then analyzed using the Statistical Program for Social Science (SPSS) version 25. Analytical evaluation is carried out through double linear regression. This study uses a quantitative method that examines a particular population or sample in the analysis of statistical data with the aim of testing a given hypothesis. In this study there are results that imply that electronic word-of-mouth (E-WOM), Service Features, and Free Delivery are some of the marketing techniques that are quite important in influencing consumers to make purchasing decisions.